2022
DOI: 10.1002/adfm.202201684
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Simultaneous X‐Ray Imaging and Dosimetry Using Phosphor‐Based Detectors with High Memory Stability and Convenient Readout Process

Abstract: Flexible X‐ray storage phosphor sheets are regarded as promising alternatives to conventional electronic flat‐panel X‐ray detectors, enabling X‐ray imaging and dosimetry in less accessible situations. However, it is a challenge to develop phosphor‐based detectors with high memory stability and convenient readout processes. Here, an approach to realize this using radiation‐induced photoluminescence tuning in (Ba1‐xSrx)2SiO4:Eu phosphors is demonstrated, ascribed to the reduction of Eu3+ toward Eu2+. The associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 72 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…Holloway et al reported that the radioluminescence intensity of Y 2 O 2 S:Eu 3+ decreased under ionizing radiation because of the low-efficiency Y 2 O 3 :Eu 3+ “dead layer” grown on the surface . Poelman et al found that (Ba 1– x Sr x ) 2 SiO 4 :Eu scintillators induced a new luminescence center through the valence change of Eu 2+ toward Eu 3+ under X-ray irradiation . Such radiation-induced luminescence tuning phenomenon may lead to a decrease in FRET efficiency between the scintillator and the photosensitizer, which results in a decrease in ROS production.…”
Section: Mechanism and Concerns Of X-pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…Holloway et al reported that the radioluminescence intensity of Y 2 O 2 S:Eu 3+ decreased under ionizing radiation because of the low-efficiency Y 2 O 3 :Eu 3+ “dead layer” grown on the surface . Poelman et al found that (Ba 1– x Sr x ) 2 SiO 4 :Eu scintillators induced a new luminescence center through the valence change of Eu 2+ toward Eu 3+ under X-ray irradiation . Such radiation-induced luminescence tuning phenomenon may lead to a decrease in FRET efficiency between the scintillator and the photosensitizer, which results in a decrease in ROS production.…”
Section: Mechanism and Concerns Of X-pdtmentioning
confidence: 99%
“…78 The decrease in a material's luminescence performance may also be due to induced absorption of the color center caused by radiation and radiation defects. 67 79 Such radiation-induced luminescence tuning phenomenon may lead to a decrease in FRET efficiency between the scintillator and the photosensitizer, which results in a decrease in ROS production. Fortunately, high-temperature sintering or hot-injection methods enabled the high crystalline nature of nanoscintillators to avoid possible defects or decomposition.…”
mentioning
confidence: 99%
“…[27][28][29][30] The well-developed passive dosimeters mainly include luminescent materials and photochromic materials. [11,17,29,[31][32][33][34][35][36][37] Luminescent materials operating on the principles of thermoluminescence (LiF:Mg,Ti and CaF 2 :Dy), optically stimulated luminescence (Al 2 O 3 :C and BeO, e.g. ), and radio-photoluminescence (Ag-doped phosphate glass and Al 2 O 3 :C,Mg, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The development of X-ray detection has caused a high research boom due to its broad application prospects in non-destructive detection and medical diagnosis. [1][2][3][4] In recent years, X-ray detectors based on semiconductors like CdTe, 𝛼-Se, Si, and CsI:Tl have experienced rather rapid development, culminating in the application of planar detection. [5,6] However, with the rapid development of wearable devices and the diversification of detected object shapes, it is urgent to develop flexible X-ray detectors.…”
Section: Introductionmentioning
confidence: 99%